Face to face two cultures meet in Aotearoa - Kessell, Terri (Tangata Whenua, 2009)
Resource for year 9 to 10 students in which students explore New Zealand history in the context of classical Māori culture, first contact with Europeans and the consequences of the interactions between the two cultures which followed. Suggested level: junior secondary